Analisis Sitasi Koleksi Perpustakaan dalam Menyusun Karya Akhir Mahasiswa Departemen Matematika Fakultas MIPA UGM - Wiyarsih Wiyarsih; Endah Choiriyah; Ismu Widarto; Masrumi Fathurrohmah; Susiana Susiana (Media Pustakawan, 2022)
The Faculty of Mathematics and Natural Sciences library provides various collections of library materials as learning resources in supporting the implementation of the Tri Darma of Higher Education. The background of this research is that the library does not yet know the citation of collections by students of the Department of Mathematics in compiling the final work. The purpose of this research is to analyze the citation of library collections which include type, language, year of publication, and availability of literature. The research method used is descriptive research with a quantitative approach. The research subject is a collection of thesis, theses, and dissertations for 2019 Mathematics Department students, while the object of research is a bibliography of the collection. Methods of data collection using the method of documentation. Analysis of the data used is descriptive quantitative analysis. The results of this analysis show the average citation of all samples of 21 citations; in the collection of literary thesis the most cited are books 50.2%, theses, books are most cited 47%, dissertations are most cited journals 61%; most of the cited literature is in English 84%; the year of publication cited is mostly the younger year, and the overall availability of literature in the sufficient category is 53%. The conclusion of this study, the most widely cited books by students of the Department of Mathematics at the S1 and S2 levels, while S3 students cite journals the most.